Isolation, Structure Determination, and Cytotoxic Activity of Steroid Compound from The Stem Bark of Aglaia cucullata (Meliaceae) - Kindi Farabi; Desi Harneti; Nurlelasari Nurlelasari; Tri Mayanti; Rani Maharani; Unang Supratman (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Steroids are one of the secondary metabolite groups that are abundant in many organisms. In plants, this type of compound is called phytosterols. Phytosterols have been widely known to show many potential bioactivities such as anti-inflammatory, induced apoptosis, cytotoxic, anti-diabetic, angiogenic, and antioxidant. One of the sources of phytosterol compounds is the genus Aglaia. As the largest genus in the Meliaceae family, the genus Aglaia contains many bioactive compounds, including steroids. This research reported the isolation, structural determination, and cytotoxic activity of steroid compounds from the stem bark of Aglaia cucullata, one of the members of the Aglaia genus. Pure isolated steroid was obtained after maceration of dried stem bark with ethanol and partitioned based on difference polarity, continued by column chromatography. Spectroscopic methods, including HRMS, FTIR, 1D and 2D NMR, were used for structural determination. The compound structure identified as stigmast-5-en-3β-ol-3β-oleate was first isolated from this species. MCF-7 breast cancer cell, B16-F10 melanoma cell, and CV-1 normal fibroblast kidney cell were used to evaluate its cytotoxicity. Stigmast-5-en-3β-ol-3β-oleate displayed low cytotoxicity against those two cancer cells and a normal cell.